تعدد الزوجات في الخطاب القرآني: دراسة تحليلة في ضوء مقاصد الشريعة = Polygamy in Qur’anic injunctions: an analytical study in the light of objectives of shari‘ah = Poligami dalam injunksi Al-Quran - Ghalia, Bouhedda; Zakariyah, Habeebullah (IIUM Press, International Islamic University Malaysia, 2016)
إن قضية تعدد الزوجات تُعَدُّ من القضايا المثيرة في عصرنا الحاضر، وذلك نتيجةً لما يشهده الواقع من اضطراب المواقف والممارسات تجاهه. ولم يقتصر الأمر على ذلك؛ بل تعدّاه إلى إعادة النظر في خطابات القرآن تجاه قضية التعدد؛ وهو المسوّغ الذي جعل بعض الباحثين يشكك في شرعية التعدد في الإسلام. وتكمن المشكلة في أن ظواهر بعض الآيات تشير إلى إباحة التعدد، بيد أن الأخرى تقيّدها بالعدل، وذلك في قوله: ﴿فَإِنْ خِفْتُمْ أَلَّا تَعْدِلُوا فَوَاحِدَةً أَوْ مَا مَلَكَتْ أَيْمَانُكُمْ ذَلِكَ أَدْنَى أَلَّا تَعُولُوا﴾، وفي الوقت نفسه ينفي ظاهر بعض الخطابات القرآنية أن العدل المنشود من المعدّد تجاه زوجاته غايةٌ لا تدرك ﴿وَلَنْ تَسْتَطِيعُوا أَنْ تَعْدِلُوا بَيْنَ النِّسَاءِ وَلَوْ حَرَصْتُمْ﴾. ومن هذا المنطلق تهدف هذه الورقة إلى كشف النقاب عن العدل المنشود في ضوء الآيات التي جاءت في قضية التعدّد في القرآن، وحيث إن هذه القضية لها أبعادها الاجتماعية في استقرار الأسرة المسلمة ،فإن هذا البحث يحاول معالجة شرعية التعدد بين النظرية والتطبيق في ضوء مقاصد الشريعة. وستنتهج الدراسة كلاّ من المنهجين الاستقرائي والتحليلي في تتبع وجمع المادة العلمية و تحليليها و تقييمها بما يسهم في بناء موقف موضوعي ووسطي تجاه القضية. *********************************************************** The issue of polygamyis among the prominent issues of our contemporary time. This is the result of the confusing opinions and practices of polygamy. The matter is not limited to this aspect; it has rather related to the insight of the Qur’anic discourses. It has become a justification for some of the researchers to doubt the SharÊ‘ah legality of polygamy in Islam. This problem is based on the evident meaning of the verses pointing towards permissibility of polygamy, whereas the other verse restricts polygamy with justice. The Qur’an states (4: 3): “But if you fear that you shall not be able to deal justly (with them), then only one, or (a captive) that your right hands possess, that will be more suitable, to prevent you from doing injustice.” At the same time, another evident Qur’anic discourse refers that the justice sought from the husband towards his wives is not achievable. The Qur’an states (4: 129): “You are never able to be fair and just as between women, even if it is you ardent desire.” From this premise, this research aims to unveil the pursued justice in the light of verses related to polygamy in theQur’an, due to the fact that this issue has a social dimension in establishing Muslim family. This work attempts to reconcile between theory and practice of legality of polygamyin the light of the SharÊ‘ahobjectives. The study drew its conclusion using both inductive and analytical methods so as to trace, collect, analyze and evaluate the relevant materials in order to build an objective and balanced position about the subject matter. ******************************************************* Isu poligami adalah antara isu yang terkenal pada masa kini. Ini disebabkan oleh pendapat dan amalan poligami yang mengelirukan. Perkara itu tidak terhad kepada aspek ini; ia berkaitan dengan wawasan wacana al-Quran. Ia telah menjadi satu justifikasi untuk beberapa penyelidik untuk meragui kesahihan Shari'ah mengenai poligami dalam Islam. Masalah ini adalah berdasarkan kepada erti yang jelas daripada ayat-ayat menunjuk kebenaran poligami, manakala ayat yanglain melarang poligami dengan adil. Al-Quran menyatakan (4: 3): "Tetapi jika kamu takut tidak akan dapat berlaku adil (dengan mereka), maka hanya satu, atau (tawanan) yang kamu miliki, yang akan menjadi lebih sesuai, untuk mengelakkan anda daripada melakukan kezaliman."Pada masa yang sama, satu lagi wacana al-Quran jelas merujuk bahawa keadilan yang diminta dari suami terhadap isteri-isterinya tidak boleh dicapai. Al -Qur'an (4: 129):”. Dan kamu tidak akan dapat berlaku adil di antara isteri-isteri kamu sekalipun kamu bersungguh-sungguh (hendak melakukannya);" Dari premis ini, kajian ini bertujuan untuk memastikan keadilan dalam ayat-ayat al-Quran yang berkaitan dengan poligami, kerana isu ini mempunyai dimensi sosial dalam membina keluarga Islam. Karya ini cuba untuk mendamaikan antara teori dan amalan kesahihan poligami menurut objektif Shari'ah. Kajian ini menyimpul dengan menggunakan kedua-dua kaedah induktif dan analisis bagi mengesan, mengumpul, menganalisis dan menilai bahan yang berkaitan untuk membina kedudukan berobjektif seimbang dengan perkara tersebut.